Program on breast self-exam knowledge among peer teachers’ mothers of a public educational institution, 2018 - Meneses Quispe, Sussan Roxana (2022)
Objective: To determine the effectiveness of a program on breast self-exam knowledge among peer teachers’ mothers of a public educational institution, 2018. Materials and methods: A quantitative and pre-experimental research conducted with 124 mothers of peer teachers attending the 4th year of secondary school at a public educational institution in 2018. Results: Fifty four point eight four percent (54.84 %) of the peer teachers were females and 45.16 % were males. Ninety-eight point four zero percent (98.40 %) of peer teachers’ mothers aged between 35 and 59 years, 66.10 % were cohabiting, 47.60 % had secondary education and 47.60 % practiced evangelism. In the pretest, breast self-exam knowledge reached an average score of 8.94 points, out of which 83.10 % showed a low level and 16.90 % a medium level. In the posttest, the average score was 13.48 points, out of which 14.52 % showed a high level, 71.77 % a medium level and 13.71 % a low one. There was a significant difference (p = 0.000) between the pretest and posttest scores of breast self-exam knowledge, which demonstrates the effectiveness of the educational program. Likewise, a significant difference was found between the pretest and posttest scores in dimensions such as knowledge of breast cancer, risk factors, diagnostic methods and breast self-exam (p = 0.000) among peer teachers’ mothers. Conclusions: Based on the results, it is concluded that the program on breast self-exam knowledge among peer teachers’ mothers of a public educational institution was effective, and the Wilcoxon signed-rank test showed a significant difference (p = 0.000).